Economic impacts of floods in China and adaptation strategies under climate change - Ying Xue; Jun Xia; Yuan Liu; Lei Zou (Environmental Research Letters)
Climate change has intensified the frequency and severity of heavy rainfall and flooding in China, posing serious threats to economic and social stability. Over the past 40 years, the increasing trend of these events has led to significant economic losses, highlighting the urgent need to develop effective adaptation strategies in both research and policy. This study used the Adaptive Regional Input–Output model to comprehensively assess the economic impacts of the July 2021 Henan flood, with a main focus on indirect economic losses (IELs) that are often underestimated in traditional assessments. The findings revealed that the IELs were up to $37.9 billion, nearly twice the direct economic losses. Additionally, a sensitivity analysis showed that increasing production capacity and the timing required to achieve it were two key factors to reduce IELs. Based on these insights, this study proposes an adaptation strategy framework tailored to China’s current development context, where systemic governance, strategic investments, and technological innovation are accounted for. This framework offers practical strategies to reduce the impacts caused by floods, thereby providing valuable guidance for sustainable disaster risk reduction and long-term economic stability in China.